2013
DOI: 10.1177/1524839913513587
|View full text |Cite
|
Sign up to set email alerts
|

Key Considerations in Designing a Patient Navigation Program for Colorectal Cancer Screening

Abstract: Colorectal cancer is the second leading cause of cancer mortality among those cancers affecting both men and women. Screening is known to reduce mortality by detecting cancer early and through colonoscopy, removing precancerous polyps. Only 58.6% of adults are currently up-to-date with colorectal cancer screening by any method. Patient navigation shows promise in increasing adherence to colorectal cancer screening and reducing health disparities; however, it is a complex intervention that is operationalized di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 29 publications
0
38
0
1
Order By: Relevance
“…While accreditation standards, health care legislation, and multiple organizations all emphasize the importance of trained patient navigators, no nationally-established certifications or standards for PN training exist, and little is known about the optimal delivery and content of training (DeGroff, Coa, Morrissey, Rohan, & Slotman, 2014; Shelton et al, 2011). Two established PN training programs exist in the United States: the Harold P. Freeman Patient Navigation Institute and the Colorado Patient Navigator Training Program, which provide training to navigators regardless of program affiliation.…”
Section: Introductionmentioning
confidence: 99%
“…While accreditation standards, health care legislation, and multiple organizations all emphasize the importance of trained patient navigators, no nationally-established certifications or standards for PN training exist, and little is known about the optimal delivery and content of training (DeGroff, Coa, Morrissey, Rohan, & Slotman, 2014; Shelton et al, 2011). Two established PN training programs exist in the United States: the Harold P. Freeman Patient Navigation Institute and the Colorado Patient Navigator Training Program, which provide training to navigators regardless of program affiliation.…”
Section: Introductionmentioning
confidence: 99%
“…In an investigation of CRC protocol and screening prevalence at 49 FQHCs in the Midwest, Daly et al 26 similarly found a significant correlation between the number of protocols employed and the percentage of patients that were screening compliant. In addition to protocol changes, DeGroff et al 27 proposed 10 key features to establish a successful CRC screening navigation program: 1) define the patient population and its unique barriers, 2) apply a theoretical framework, 3) establish entry and exit points for navigation services, 4) determine a location where navigation services will be performed, 5) provide communication training, 6) identify the navigation services offered and navigator responsibilities, 7) determine qualifications for the navigator, 8) design navigator training, 9) identify navigation supervision, and 10) evaluate navigation services.…”
Section: Discussionmentioning
confidence: 99%
“…In primary care, tailored interventions for patients are especially likely to be effective in increasing colorectal cancer screening in primary care [29–31]. The use of lay or nurse cancer screening navigators is also likely to be helpful [32–35]. Horne et al [36] examined the effect of patient navigation on increasing colorectal cancer screening among older African Americans.…”
Section: Methodsmentioning
confidence: 99%